2021
DOI: 10.3390/ma14040953
|View full text |Cite
|
Sign up to set email alerts
|

Process Design for a Production of Sustainable Materials from Post-Production Clay

Abstract: Alkali activated cement (AAC) can be manufactured from industrial by-products to achieve goals of “zero-waste” production. We discuss in detail the AAC production process from (waste) post-production clay, which serves as the calcium-rich material. The effect of different parameters on the changes in properties of the final product, including morphology, phase formation, compressive strength, resistance to the high temperature, and long-term curing is presented. The drying and grinding of clay are required, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In earlier studies, we showed the beneficial effect of grinding the raw materials, even if the process is energy-intensive; the reduction of particle size and the increase of specific surface area were crucial to obtaining the higher reaction rate of the precursor, more reacted final material and the proper mechanical properties of the geopolymer products [80]. The size reduction throughout the milling process is recognized as a mechanical activation of the material, resulting in an increase in compressive strength [75,79].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In earlier studies, we showed the beneficial effect of grinding the raw materials, even if the process is energy-intensive; the reduction of particle size and the increase of specific surface area were crucial to obtaining the higher reaction rate of the precursor, more reacted final material and the proper mechanical properties of the geopolymer products [80]. The size reduction throughout the milling process is recognized as a mechanical activation of the material, resulting in an increase in compressive strength [75,79].…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, the crystalline quartz phase, due to the aluminosilicate compounds, can improve the physical and mechanical properties of geopolymers [99]. The kaolinite in MK may demonstrate an incomplete calcination process, which is dependent on the temperature treatment [80,100,101]. The asymmetrical hump appearing clearly in the range of 20-30 • (2θ) is commonly identified in MKs and indicates an amorphous phase related to aluminosilicate glass (Figure S4 in the Supplementary Materials) [85,102].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the final geopolymer properties may be the complementary result of both factors-the total content of Si and Al components but also the modifying effect of CaO [21]. FFAs can be classified as; (i) silica-aluminum, (ii) alumina-silica, (iii) calcium sulphate, and (iv) calcium types [43,44]. According to the results, both FFAs can be defined as an alumina-silica type.…”
Section: The Properties Of Raw Materialsmentioning
confidence: 99%
“…Generally, the raw material reactivity was controlled by numerous intrinsic (e.g., the mineralogical, chemical, structural composition, amount of reactive fraction of SiO 2 and Al 2 O 3 ) and extrinsic parameters (e.g., FA fineness level, type and proportion of raw materials, the ratio of activators, duration and temperature of the process) (Figure 1, Tables 2, 3 and 5), which consequently affected GPBM mechanical properties and homogeneity (Table 5). It is well known that a greater fineness level of the FFA increases paste workability and the rate of geopolymerization, shortens setting time, and improves physical (density), mechanical (compressive and flexural strength), and microstructural (compact and uniform matrix) properties of the geopolymer [21,44]. The mechanism of improving the physical and mechanical properties of GPBM is also attributed to a higher amount of alkaline aluminosilicate gel [21,[49][50][51][52].…”
Section: Gpbms Production and Propertiesmentioning
confidence: 99%